A REVIEW ON THE ROLE OF TRIGLYCERIDE IN METABOLIC SYNDROME - ABDOLJALAL MARJANI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Increased serum triglyceride levels are commonly observed in subjects with metabolic syndrome (MS). Many studies show that hypertriglyceridemia is forcefully collaborated with all components of MS. The aim of this study was to review the role of triglyceride in MS. Based on prior epidemiological studies, this review indicates association of high triglyceride levels with cardiovascular disease (CVD). On the other hand, it is clearly shown that CVD is one of the main causes of death worldwide. Thus, it is important to investigate about MS and its components to decrease the prevalence of MS among different. Keywords: Triglycerides, Risk factors, Metabolic syndrome, Cardiovascular disease.